Transforming Hospital Administration In 2026: A Literature Review On Innovation, Efficiency, And Patient-Centered Leadership - Aulia Dini Ayuningtias; Nur Mahliza; Reva Nazwa Zahara (Journal of Innovative and Creativity, 2026)
The study purpose was to explore how innovation, operational efficiency, and patient-centered leadership collectively shape hospital administration in 2026. The global healthcare landscape is undergoing rapid transformation, driven by digital technologies, data analytics, and evolving patient expectations. This literature review examines how hospital administrators are integrating technological advancement with adaptive leadership to improve organizational performance and patient outcomes. The review focuses on identifying key strategies that enable healthcare institutions to balance technological efficiency with the human dimensions of care. Materials and methods. A systematic literature review was conducted following PRISMA 2020 guidelines. Peer-reviewed articles published between 2019 and 2026 were retrieved from databases including PubMed, Scopus, Web of Science, and Google Scholar. Studies were included if they addressed hospital administration, innovation, efficiency, or leadership within healthcare systems. Twenty-four high-quality studies were selected for qualitative synthesis. Data were analyzed thematically across three domains: digital innovation, operational efficiency, and patient-centered leadership. Results. Findings revealed that digital transformation, when supported by adaptive and empathetic leadership, significantly improves hospital efficiency, staff engagement, and patient satisfaction. Integration of AI, Lean Six Sigma, and data-driven governance models led to measurable gains in workflow optimization and service quality. Leadership practices emphasizing transparency, trust, and collaboration were found to mediate the success of innovation initiatives. Conclusions. The transformation of hospital administration in 2026 is defined by the fusion of technology and human-centered leadership. Sustainable progress depends not only on digital tools but on leaders’ capacity to align innovation with empathy and organizational purpose. The review concludes that hospitals fostering patient-centered, adaptive leadership cultures are best positioned to thrive in an era of complex healthcare transformation.